Are healthcare costs from obesity associated with body mass index, comorbidity or depression? Cohort study using electronic health records. Issue 3 (21st April 2016) - Rudisill, C.; Charlton, J.; Booth, H. P.; Gulliford, M. C.
Summary: The objective of this study was to evaluate the association between body mass index (BMI) and healthcare costs in relation to obesity‐related comorbidity and depression. A population‐based cohort study was undertaken in the UK Clinical Practice Research Datalink (CPRD). A stratified random sample was taken of participants registered with general practices in England in 2008 and 2013. Person time was classified by BMI category and morbidity status using first diagnosis of diabetes (T2DM), coronary heart disease (CHD), stroke or malignant neoplasms. Participants were classified annually as depressed or not depressed. Costs of healthcare utilization were calculated from primary care records with linked hospital episode statistics. A two‐part model estimated predicted mean annual costs by age, gender and morbidity status. Linear regression was used to estimate the effects of BMI category, comorbidity and depression on healthcare costs. The analysis included 873 809 person‐years (62% female) from 250 046 participants. Annual healthcare costs increased with BMI, to a mean of £456 (95% CI 344–568) higher for BMI ≥40 kg m −2 than for normal weight based on a general linear model. After adjusting for BMI, the additional cost of comorbidity was £1366 (£1269–£1463) and depression £1044 (£973–£1115). There was evidence of interaction so that as the BMI category increased, additional costs of comorbidity (£199, £74–£325) or depression (£116, £16–£216) were greater. High healthcare costs in obesity may be driven by the presence of comorbidity and depression. Prioritizing primary prevention of cardiovascular disease and diabetes in the obese population may contribute to reducing obesity‐related healthcare costs.